Prevalence and clinical significance of red flags in patients with hypertrophic cardiomyopathy. (15th January 2020) - Limongelli, Giuseppe; Monda, Emanuele; Tramonte, Stefania; Gragnano, Felice; Masarone, Daniele; Frisso, Giulia; Esposito, Augusto; Gravino, Rita; Ammendola, Ernesto; Salerno, Gemma; Rubino, Marta; Caiazza, Martina; et al.
Abstract: Introduction: We sought to determine prevalence and predictive accuracy of clinical markers (red flags, RF), known to be associated with specific systemic disease in a consecutive cohort of patients with hypertrophic cardiomyopathy (HCM). Methods: We studied 129 consecutive patients (23.7 ± 20.9 years, range 0–74 years; male/female 68%/32%). Pre-specified RF were categorized into five domains: family history; signs/symptoms; electrocardiography; imaging; and laboratory. Sensitivity (Se), specificity (Sp), negative predictive value (NPV), positive predictive value (PPV), and predictive accuracy of RF were analyzed in the genotyped population. Results: In the overall cohort of 129 patients, 169 RF were identified in 62 patients (48%). Prevalence of RF was higher in infants (78%) and in adults >55 years old (58%). Following targeted genetic and clinical evaluation, 94 patients (74%) had a definite diagnosis (sarcomeric HCM or specific causes of HCM). We observed 14 RF in 13 patients (21%) with sarcomeric gene disease, 129 RF in 34 patients (97%) with other specific causes of HCM, and 26 RF in 15 patients (45%) with idiopathic HCM ( p  < 0.0001). Non-sarcomeric causes of HCM were the most prevalent in ages <1yo and > 55yo. Se, Sp, PPV, NPV and PA of RF were 97%, 70%, 55%, 98% and 77%, respectively. Single and clinical combination of RF (clusters) had an high specificity, NPV and predictive accuracy for the specific etiologies (syndromes/metabolic/infiltrative disorders associated with HCM). Conclusions: An extensive diagnostic work up, focused on analysis of specific diagnostic RF in patients with unexplained LVH facilitates a clinical diagnosis in 74% of patients with HCM. Highlights: In the overall cohort, prevalence of red flags (RF) was 48%. Prevalence of red flags (RF) was higher in infants (78%) and in adults >55 years old (58%). Se, Sp, PPV, NPV and PA of RF in the overall cohort were 97%, 70%, 55%, 98% and 77%, respectively. Single and clinical combination of red flags RF (clusters) had a high Sp, NPV and PA for the specific etiologies An extensive diagnostic work-up focused on analysis of RF facilitates a clinical diagnosis in 74% of patients with HCM.